Revision and description of select Mesozoic actinopterygians from the Sydney, Great Artesian and Perth basins of Australia. - Berrell, Rodney William (Curtin University, 2023)
Mesozoic sites across Australia were surveyed with four new genera of actinopterygian (bony fish) being discovered and described. Two historically identified fish were also redescribed and placed in a modern phylogenetic context. The research identified biogeographic links in the fauna between Australian and South America which suggests faunal exchange between east and west Gondwana during the Mesozoic.